The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1136/bmjopen-2017-020031
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in maternally perceived fetal movement and their association with late stillbirth: findings from the Midland and North of England stillbirth case–control study

Abstract: ObjectiveTo report perception of fetal movements in women who experienced a stillbirth compared with controls at a similar gestation with a live birth.DesignCase–control study.Setting41 maternity units in the UK.ParticipantsCases were women who had a late stillbirth ≥28 weeks gestation (n=291) and controls were women with an ongoing pregnancy at the time of the interview (n=733). Controls were frequency matched to cases by obstetric unit and gestational age.MethodsData were collected using an interviewer-admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
53
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 39 publications
3
53
0
Order By: Relevance
“…The participating maternity units serve an ethnically and socially diverse population, suggesting these findings may be generalizable. However, the study recruited fewer women than anticipated, the incidence of 0.45% of women being much lower than 9.6% reported in a prospective study from China 13 and 6.9% of controls in MiNESS 4 . As women perceiving IFM are not routinely asked to contact maternity services in the UK, women perceiving this symptom may not have been recruited.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…The participating maternity units serve an ethnically and socially diverse population, suggesting these findings may be generalizable. However, the study recruited fewer women than anticipated, the incidence of 0.45% of women being much lower than 9.6% reported in a prospective study from China 13 and 6.9% of controls in MiNESS 4 . As women perceiving IFM are not routinely asked to contact maternity services in the UK, women perceiving this symptom may not have been recruited.…”
Section: Discussionmentioning
confidence: 95%
“…In recent years, evidence has emerged to suggest that maternal perception of a single episode of abnormally increased fetal movements (IFM) may be associated with stillbirth, 4‐8 with a twofold, 4 fourfold 5 and sevenfold 6 risk of stillbirth, respectively. Importantly, only a single episode of IFM is associated with an increased risk of stillbirth, with multiple episodes of IFM being protective 4‐6 . This has led to the suggestion that a single episode of IFM could represent an acute in utero event 9 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2015, the stillbirth rate in the UK ranked 24th out of 49 high-income countries [1] and while the rate has declined over recent years [2], further reduction is a national priority [3]. Maternal perception of reduced fetal movements (RFM) is associated with stillbirth [3][4][5][6][7] and is thought to be a symptom of placental dysfunction restricting the supply of nutrients or oxygen to the fetus [8,9]. A systematic review of management for RFM concluded that there was insufficient evidence to guide practice and that highquality trials were required [10].…”
Section: Introductionmentioning
confidence: 99%
“…A similar case-control study in the U.K. found that women who reported decreased frequency of fetal movements (without increase of strength) in the last 2 weeks were at increased risk of stillbirth (aOR 4.51, 95% CI: 2.38-8.55) 39 . A further study by O'Sullivan et al described a 2to 3-fold increased risk of stillbirth in women presenting with DFM and a live baby 40 .…”
Section: Decreased Fetal Movement and Stillbirthmentioning
confidence: 91%